Television: Media for Islamic Education in Millennium Era - Mu'amalah, Mu'amalah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
The advances in technology and communication have affected almost all aspects of human life, including Islamic education. Television has become one of the products of this technological progress, bringing its advantages such as its audio-visual nature. The ability to reach the public has brought benefits in the education sector, especially Islamic education. In other words, the media have been able to provide Islamic education to the people of Indonesia. Television programs presented are able to manifest as textbooks with Islamic content, while the actors and figures presented were forms of teachers on television. Islamic studies on television can be seen in different events, ranging from tele-da'wah programs, music (nasyid, shalawat, and qasidah), operas and films, and other entertainment programs.